PENGARUH PENAMBAHAN CaCO3 DAN WAKTU PENYIMPANAN TERHADAP KADAR VITAMIN C PADA PROSES PENGHAMBATAN PEMATANGAN BUAH TOMAT (Lycopersicum esculentum Mill) - Rudi Kartika (JURNAL KIMIA MULAWARMAN, 2010)
The aim of this research is to know the influence of CaCO3 addition and storage duration to vitamine C concentrate in ripe obstruction process of tomato (Lycopersicum esculentum Mill). Calcium carbonate(CaCO3) which is added 0; 0.2; 0.4; 0.6 and 0.8 percent of weight and storage duration were 0; 2; 4; 6; 8; 10 and 12 days. Vitamine C was determined by using iodometric titration method. The data obtained were then analized by ANOVA test and LSD test. The result showed that CaCO3 addition could influence vitamine C concentrate in ripe obstruction process of tomato (Lycopersicum esculentum Mill) on standard 5% and 1% with  Ftest > Ftabel (5% and 1%) or F(7.6667) > F(2.50 and 3.60) and storage duration could influence vitamine C concentrate in ripe obstruction process of tomato (Lycopersicum esculentum Mill) on standard 5% and 1% with Ftest > Ftabel (5% and 1%) or F(1204.2222) > F(2.32 and 3.07). Based on the result LSD test on significant standard 5% (0.0143) and 1% (0.0190), optimum vitamine C concentrate were 0.8589 mg/10 g on 0.2% of calcium carbonate (CaCO3) addition and 10 days of storage duration.Keywords : ANOVA, CaCO3, LSD, tomato, vitamine C, storage duration